Integrating ‘undetectable equals untransmittable’ into HIV counselling in South Africa: the development of locally acceptable communication tools using intervention mapping - (:unkn) unknown (My University, 2024)
Abstract Background The global campaign for “Undetectable equals Untransmittable” (U = U) seeks to spread awareness of HIV treatment as prevention, aiming to enhance psychological well-being and diminish stigma. Despite its potential benefits, U = U faces challenges in Sub-Saharan Africa, with low awareness and hesitancy to endorse it. We sought to develop a U = U communications intervention to support HIV counselling in primary healthcare settings in South Africa. Methods We used Intervention Mapping (IM), a theory-based framework to develop the “Undetectable and You” intervention for the South African context. The six steps of the IM protocol were systematically applied to develop the intervention including a needs assessment consisting of a systematic review and qualitative research including focus group discussions (FGD) and key informant (KI) interviews. Program objectives and target population were determined before designing the intervention components and implementation plan. Results The needs assessment indicated low global U = U awareness, especially in Africa, and scepticism about its effectiveness. Lay counsellors and clinic managers stressed the need for a simple and standardized presentation of U = U addressing both patients’ needs for encouragement and modelling of U = U success but also clear guidance toward ART adherence behaviour. Findings from each step of the process informed successive steps. Our final intervention consisted of personal testimonials of PLHIV role models and their partners, organized as an App to deliver U = U information to patients in primary healthcare settings. Conclusions We outline an intervention development strategy, currently in evaluation stage, utilizing IM with formative research and input from key U = U stakeholders and people living with HIV (PLHIV).
Keywords: African Research